Fast Parallel Equivalence Relations in a Datalog Compiler - Nappa, Patrick; Zhao, David; Subotic, Pavle; Scholz, Bernhard (Proceedings / International Conference on Parallel Architectures and Compilation Techniques, 2019)
Modern parallelizing Datalog compilers are employed in industrial applications such as networking and static program analysis. These applications regularly reason about equivalences, e.g., computing bitcoin user groups, fast points-to analyses, and optimal network routes. State-of-the-art Datalog engines represent equivalence relations verbatim by enumerating all possible pairs in an equivalence class. This approach inhibits scalability for large datasets. In this paper, we introduce EQREL, a specialized parallel union-find data structure for scalable equivalence relations, and its integration into a Datalog compiler. Our data structure provides a quadratic worst-case speed-up and space improvement. We demonstrate the efficacy of our data structure in SOUFFLÉ, which is a Datalog compiler that synthesizes parallel C ++ code. We use real-world benchmarks and show that the new data structure scales on shared-memory multi-core architectures storing up to a half-billion pairs for a static program analysis scenario.